2021
DOI: 10.1111/bjh.17377
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic microangiopathy in untreated myeloma patients receiving carfilzomib, cyclophosphamide and dexamethasone on the CARDAMON study

Abstract: Proteasome inhibitors have been associated with thrombotic microangiopathy (TMA)a group of disorders characterised by occlusive microvascular thrombosis causing microangiopathic haemolytic anaemia, thrombocytopenia and end-organ damage. To date, carfilzomib-associated TMA has predominantly been described in relapsed/refractory myeloma patients. We report eight patients with newly diagnosed myeloma who experienced TMA events while receiving carfilzomib on the phase II CAR-DAMON trial. The first three occurred d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
(98 reference statements)
0
8
0
Order By: Relevance
“…The CARDAMON study, a phase II trial of carfilzomib, cyclophosphamide, and dexamethasone in untreated myeloma patients, reported TMA in eight out of 281 patients. ADAMTS13 activity was checked in seven of these eight patients, and all had normal activity [ 19 ]. Lastly, Fotiou et al reported TMA in six out of 114 patients (5%) with relapsed and refractory myeloma multiple myeloma who received carfilzomib.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The CARDAMON study, a phase II trial of carfilzomib, cyclophosphamide, and dexamethasone in untreated myeloma patients, reported TMA in eight out of 281 patients. ADAMTS13 activity was checked in seven of these eight patients, and all had normal activity [ 19 ]. Lastly, Fotiou et al reported TMA in six out of 114 patients (5%) with relapsed and refractory myeloma multiple myeloma who received carfilzomib.…”
Section: Discussionmentioning
confidence: 99%
“…Carfilzomib-induced TMA has been reported as early as 24 h and as late as 24 months after therapy [ 19 ]. In this report, our patient presented on cycle 1, day 6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the incidence of TMA disorders is low, reaching up to 2.8% in patients receiving carfilzomib plus cyclophosphamide and dexamethasone in the phase 2 CARDAMON trial, our experience suggests that a high index of suspicion for carfilzomib-induced TMA is warranted in the real-world setting. 8 TMA syndromes, including TTP, HUS, and DITMA, are characterized by microvascular endothelial injury and thrombosis leading to thrombocytopenia and microangiopathic hemolytic anemia. 5,9 Several drug culprits of DITMA are recognized, including quinine, gemcitabine, tacrolimus, and proteasome inhibitors (bortezomib, carfilzomib, ixazomib).…”
Section: Discussionmentioning
confidence: 99%